2021
DOI: 10.46300/91011.2021.15.38
|View full text |Cite
|
Sign up to set email alerts
|

Our Experience in the Treatment of Vertebrobasilar Insufficiency Due to Cervical Spine Disorders

Abstract: This article defines vertebra-related causes of vertebrobasilar insufficiency in patients with the signs of tortuosity of segment VI of the VA. The aim of this study is to present the results of diagnostics of discirculatory phenomena in the vertebrobasilar system and to show their importance for differentiated surgical treatment of stenotic lesions of segment V1 of VA in pathological disorders of cerebral circulation in the VBS caused by osteochondrosis of the cervical spine. The following traditional methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In general, there is no consensus regarding treatment for VBI [ 2 ]. However, common medical practices include anticoagulant and antiplatelet therapies, statins, blood pressure control [ 2 , 27 ], and lifestyle recommendations, including avoidance of smoking, and diet and exercise [ 17 ]. Endovascular treatments, including percutaneous transluminal angioplasty, stenting, and thrombectomy, are emerging as minimally invasive procedures for symptomatic vertebral artery stenosis [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, there is no consensus regarding treatment for VBI [ 2 ]. However, common medical practices include anticoagulant and antiplatelet therapies, statins, blood pressure control [ 2 , 27 ], and lifestyle recommendations, including avoidance of smoking, and diet and exercise [ 17 ]. Endovascular treatments, including percutaneous transluminal angioplasty, stenting, and thrombectomy, are emerging as minimally invasive procedures for symptomatic vertebral artery stenosis [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent randomized controlled trial and systematic review found no significant differences with respect to stroke-related disability [ 29 ] and likelihood of stroke or transient ischemic attack with these therapies compared with standard medical treatment, suggesting that further research is needed [ 28 ]. Accordingly, endovascular treatments are typically reserved for those with a high grade of stenosis, persistent symptoms despite medical treatment, and/or stenosis at the vertebral artery origin [ 2 , 27 ]. To date, acupuncture has limited evidence for treating VBI [ 30 ].…”
Section: Introductionmentioning
confidence: 99%